EDUKASI PENINGKATAN PENGETAHUAN KELUARGA DALAM PERAWATAN DIRI PASIEN GAGAL JANTUNG: EDUKASI PENINGKATAN PENGETAHUAN KELUARGA DALAM PERAWATAN DIRI PASIEN GAGAL JANTUNG - Ahmad Fauziansyah Zian; Mohammad Fahrul Arifin Arifin; Kusno Ferianto Kusno; Lukman Hakim Lukman (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2024)
Heart failure in Indonesia is a problem that causes a lot of pain and death. Heart failure sufferers often experience a decrease in their ability to function and experience shortness of breath (dyspnea) during activity or at rest. Activity patterns in heart failure sufferers are very limited, activity patterns will change, especially if the patient experiences severe breathing difficulties. This condition causes heart failure patients to experience a decrease in their ability to carry out daily activities. The healing process for heart failure patients needs to be carried out comprehensively and involve family members. The aim of this community service program is to increase family support in caring for the daily activities of heart failure patients during rehabilitation. The method used in this activity is direct health education to family members of heart failure patients. The result of this awareness program is to help families get complete information about the importance of family support in the daily care of heart failure patients to facilitate recovery and improve quality of life.